2004
DOI: 10.1016/j.asr.2003.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Solar energetic particle variations

Abstract: In the largest solar energetic-particle (SEP) events, acceleration occurs at shock waves driven out from the Sun by coronal mass ejections (CMEs). In fact, the highest proton intensities directly measured near Earth at energies up to -1 GeV occur at the time of passage of shocks, which arrive about a day after the CMEs leave the Sun. CMEdriven shocks expanding across magnetic fields can fill over half of the heliosphere with SEPs. Proton-generated Alfven waves trap particles near the shock for efficient accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 32 publications
0
65
0
Order By: Relevance
“…During intense solar particle events, the flux of solar energetic particles associated with solar flares and coronal mass ejections will likely exceed the predicted pickup ion fluxes. However, on average, these solar events only occur a few times a month [Reames, 2004;Jun et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During intense solar particle events, the flux of solar energetic particles associated with solar flares and coronal mass ejections will likely exceed the predicted pickup ion fluxes. However, on average, these solar events only occur a few times a month [Reames, 2004;Jun et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that hot O atoms undergo no collisions above 300 km, exospheric densities are calculated using Liouville's theorem [Schunk and Nagy, 2009], where the energy distribution function is fed into a Liouville code to find the hot O number density as a function of altitude in the Martian exosphere out to 100 R M . This is done separately for the bound and escaping portions of the distribution.…”
Section: Description Of the Hot Oxygen Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For the very largest events, SEP ionization of the polar atmosphere produces nitrates that precipitate to become trapped in the Earth's polar ice. Ice core analysis revealed that the largest SEP event in the last 400 years appears to be related to the giant flare observed by Carrington in 1859 (Reames, 2004). Forecasting such extraordinary events is still not possible, for two main reasons: 1) We have not yet identified unique signatures for the driving flare that would indicate an imminent explosion and its probable onset time, location, and strength, and 2) the size of the SEP fluxes is highly variable and appears to be only loosely related to the strength of the flare.…”
Section: Solar Energetic Particles (Seps)mentioning
confidence: 99%
“…The time profile of the strong SEP proton flux event of November 4, 2001 (from Reames, 2004) is shown in Figure 22. After a steep flux increase within minutes after flare onset, the fluxes in the low energy bands remain about constant for several hours while for higher energies the fluxes gradually drop, i.e., the energy spectra become steeper.…”
Section: Seps: Protons and Other Ionsmentioning
confidence: 99%